Pengaruh Media Sosial Terhadap Kesehatan Mental Dewasa Awal di Bekasi - Ardi Gumara; Fionna C A Uguy; Ade Ratri Fitria; Rijal Abdillah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This study was conducted to understand the impact of social media on the mental health of early adults in Bekasi. Social media has become an inseparable part of individuals' daily lives, and its impact on mental health needs further investigation. This research employs a quantitative method with data collected through questionnaires completed by 62 early adult respondents in Bekasi. Data analysis was conducted using the Independent Sample T-Test and correlation tests. In this study, we found no significant relationship between mental health and gender, indicating that both men and women are equally vulnerable to the negative effects of social media on mental health. However, there was a significant relationship between age and frequency of social media use with mental health, where older respondents exhibited better mental health conditions. Conversely, higher frequency of social media use correlated with a decline in mental health quality. These findings also indicate that excessive social media use can have a negative impact on the mental health of early adults, possibly due to factors such as exposure to negative content, social comparison, and addiction. This study emphasizes the importance of balanced and responsible social media use to maintain the mental health of early adults.